Assessment of serum biomarker changes following the COVID-19 pandemic and vaccination: a cohort study in Sylhet, Bangladesh - Shangida Akther; Fairoz Samiha; Sabrina Amita Sony; Mohammad Anamul Haque; Mohammad Abul Hasnat; S. M. Saiful Islam; Shamim Ahmed; Mohammad Abdullah-Al-Shoeb (Frontiers in Public Health, 2025)
ObjectivesCoronavirus 2019 (COVID-19) has spread throughout the world and the current COVID-19 vaccines have shown to be the most effective means of combating the COVID-19. This study focused to examine the status of serum biomarkers in individuals infected and non-infected with SARS-CoV-2, both before and after COVID-19 pandemic and vaccination.MethodsThis study comprised 133 adults aged 35 and older including both academic and non-academic personnel associated with Shahjalal University of Science and Technology in Sylhet, Bangladesh. Participants were evaluated before and after COVID-19 pandemic, as well as following two doses of vaccination. Blood samples were collected to measure different serum biomarkers, including fasting blood sugar (FBS), serum creatinine, serum alanine transaminase (ALT), total cholesterol (TC), triglyceride (TG), Low density lipoprotein-cholesterol (LDL-C), and High density lipoprotein-cholesterol (HDL-C). Statistical analysis was performed using SPSS software.ResultIn all participants, serum creatinine, FBS and TC levels significantly increased after two doses of vaccination (p = 0.022, 0.006, 0.05) compared to pre-vaccination levels. Notably, all serum biomarkers showed a significant elevation (p ≤ 0.05) in the self-reported SARS-CoV-2 infected group (n = 44). Additionally, 31% of participants were newly diagnosed with hyperglycemia after receiving the COVID-19 vaccine.ConclusionThe findings indicate that both self-reported SARS-CoV-2 infection and COVID-19 vaccination could influence different serum biomarker levels. However, further comprehensive research is necessary to discern the precise factors contributing to the alterations observed in the serum biomarker levels for future health management strategy.